Management of food allergies in children in South Africa : determining aspects of the knowledge and practices of dietitians and medical doctors - Stear, Georgina Isabel Jane (Stellenbosch : University of Stellenbosch, 2011)
Thesis (M Nutr)--University of Stellenbosch, 2011.